Extrapyramidal side effects with low doses of amisulpride - Mandal, Nikhiles (Medknow Publications & Media Pvt Ltd, 2014)
Amisulpride, the newly introduced antipsychotic in India, is claimed to be effective in both positive and negative symptom schizophrenia and related disorders, though it has little or no action on serotonergic receptors. Limbic selectivity and lower striatal dopaminergic receptor binding capacity causes very low incidence of EPS. But, in clinical practice, we are getting EPS with this drug even at lower doses. We have reported three cases of akathisia, acute dystonia, and drug-induced Parkinsonism with low doses of amisulpride. So, we should keep this side effect in mind when using amisulpride. In fact, more studies are required in our country to find out the incidence of EPS and other associated mechanism.